BORROWING STRATEGY IN SCIENCE FICTION TRANSLATION ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Borrowing is a crucial strategy in the translation of science fiction literature, allowing translators to preserve the originality and innovative linguistic features of source texts. By directly importing terms, neologisms, or culturally specific expressions from the source language, translators maintain lexical fidelity and stylistic authenticity. This article examines the theoretical foundations and practical applications of borrowing in science fiction translation. Through case studies of notable works, the study illustrates both the advantages and potential challenges of borrowing, including reader comprehension and consistency. The findings highlight that strategic borrowing enhances narrative integrity and supports the international dissemination of science fiction.